PENGUATAN KOMUNIKASI UNTUK ORANG DENGAN GANGGUAN JIWA DI YAYASAN EFATA YOGYAKARTA - Ningrum, Dyaloka Puspita; Putra, Ariandi; Arrianie, Lely (Jurnal Abdi Insani, 2024)
As social creatures, humans need continuous interaction with each other. However, this cannot run normally in social life when they experience mental disorders which of course cause obstacles to the process of effective interpersonal communication. In fact, sufferers find it very difficult to open up and tend to receive inadequate acceptance from the social environment. This Community Service activity was carried out at the Efata Yogyakarta Foundation with the aim of reducing negative views towards people with mental disorders as well as providing a humanist approach in an effort to restore the mental health of patients at that place. Using discussion methods and interactive simulations, this activity was attended by all 30 patients with different medical symptoms. The activity facilitators conducted (1) question and answer sessions (2) carried out art therapy and (3) practiced music therapy. By optimizing direct interaction, in an orderly manner and taking turns the target group has the courage to show themselves with their respective talents, especially in singing and coloring activities together. Ironically, this kind of visit was actually the first activity carried out by an outside party for the Efata Yogyakarta foundation. So it is hoped that this activity can continue to be supported by all parties, not only the government, the community in the surrounding environment, and even all citizens as it provides a decent life and comfort for those who have so far been more marginalized.